CYP712K4 Catalyzes the C-29 Oxidation of Friedelin in the Maytenus ilicifolia Quinone Methide Triterpenoid Biosynthesis Pathway - Bicalho, Keylla U [UNESP]; Santoni, Mariana M [UNESP]; Arendt, Philipp; Zanelli, Cleslei F [UNESP]; Furlan, Maysa [UNESP]; Goossens, Alain; Pollier, Jacob (Oxford University Press (OUP), 2019)
The native Brazilian plant Maytenus ilicifolia accumulates a set of quinone methide triterpenoids with important pharmacological properties, of which maytenin, pristimerin and celastrol accumulate exclusively in the root bark of this medicinal plant. The first committed step in the quinone methide triterpenoid biosynthesis is the cyclization of 2,3-oxidosqualene to friedelin, catalyzed by the oxidosqualene cyclase friedelin synthase (FRS). In this study, we produced heterologous friedelin by the expression of M. ilicifolia FRS in Nicotiana benthamiana leaves and in a Saccharomyces cerevisiae strain engineered using CRISPR/Cas9. Furthermore, friedelin-producing N. benthamiana leaves and S. cerevisiae cells were used for the characterization of CYP712K4, a cytochrome P450 from M. ilicifolia that catalyzes the oxidation of friedelin at the C-29 position, leading to maytenoic acid, an intermediate of the quinone methide triterpenoid biosynthesis pathway. Maytenoic acid produced in N. benthamiana leaves was purified and its structure was confirmed using high-resolution mass spectrometry and nuclear magnetic resonance analysis. The three-step oxidation of friedelin to maytenoic acid by CYP712K4 can be considered as the second step of the quinone methide triterpenoid biosynthesis pathway, and may form the basis for further discovery of the pathway and heterologous production of friedelanes and ultimately quinone methide triterpenoids.
Keywords: Celastrol; CYP712K4; Friedelin; Maytenoic acid; Maytenus ilicifolia; Quinone methide triterpenoids